2019
DOI: 10.1002/er.4528
|View full text |Cite
|
Sign up to set email alerts
|

Study of morphological characteristics on hydrophilicity‐enhanced SiO 2 /Nafion composite membranes by using multimode atomic force microscopy

Abstract: Summary Air‐breathing proton exchange membrane fuel cells (AB‐PEMFCs) have a great potential for commercialization owing to their simple mechanical configuration and low cost compared with traditional proton exchange membrane fuel cells (PEMFCs). However, AB‐PEMFCs perform worse than traditional PEMFCs owing to the omission of the humidifier and a poor air supply system. In this study, hygroscopic metal oxide materials with good water absorption characteristics were employed in a Nafion membrane without humidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…From this, it can be surmised that the area of the ionic channels on the surface of a wet membrane increases by ~80% compared with that on a dry membrane. Previous experimental results have shown that there is an approximately 80% difference between proton conductivity in ambient conditions and fully humid conditions [31,32]. Hence, our calculations are consistent with the literature.…”
Section: Analysis and Conclusionsupporting
confidence: 92%
See 1 more Smart Citation
“…From this, it can be surmised that the area of the ionic channels on the surface of a wet membrane increases by ~80% compared with that on a dry membrane. Previous experimental results have shown that there is an approximately 80% difference between proton conductivity in ambient conditions and fully humid conditions [31,32]. Hence, our calculations are consistent with the literature.…”
Section: Analysis and Conclusionsupporting
confidence: 92%
“…In this study, we determined the local charge density of a proton exchange membrane, which is directly related to the ionic domain, using an approximation model, and phase lag values obtained from electrostatic force microscopy. We also studied the variation of ionic channel networks in Nafion membranes in different conditions, with the results agreeing well with those of previous studies [31]. The enhancement of proton conductivity is prime purpose of developing the proton exchange membranes.…”
Section: Analysis and Conclusionsupporting
confidence: 86%
“…Referring to Table 3, water uptake for Nafion 117 was 44.61%, whereas that for recast Nafion and composite membranes N/E‐1, N/E‐3 and N/E‐5 were 72.48%, 73.91%, 87.27% and 77.24%, respectively. Composite membranes showed higher water uptake than the pristine Nafion membrane owing to the hygroscopic nature of carbonate particles 56 . An increasing trend was observed as the loading weight of filler increased from 1 to 3 wt% and then plummeted as the loading weight was further upsurged to 5 wt%.…”
Section: Resultsmentioning
confidence: 94%
“…Tapping-mode atomic force microscopy (AFM) was further utilized to detect the surface morphology and nanophase separation structure of hybrid membranes. [18] As seen from Figure 1c,d and Figure S8-S11, all RN,Nafion-Bi 12 -3 % and Nafion-Bi 12 -5 %h ybrid membranes show typical fingerprint images of surface morphology with the height of about 0nmt o4 .8 nm, in which the dark and bright districts represent the hydrophilic ionic nanophase and hydrophobic Nafion-backbone nanophase,r espectively.C ompared with RN,t he Nafion-Bi 12 -3 %m embrane exhibited the enhanced connectivity for both the hydrophilic and hydrophobic nanophases,a nd the hydrophilic channels were significantly widened after {H 6 Bi 12 O 16 }a ddition. However,f or the Nafion-Bi 12 -5 %m embrane,t he excessively added {H 6 Bi 12 O 16 } clusters disturb the hydrophobic/hydrophilic nano-phases, which are also demonstrated by the apparent irregularity in the surface roughness ( Figure 1d and Figure S10-S11).…”
Section: Microscopic Phase Separation Of Hybrid Membranementioning
confidence: 84%